The Impact of Blood Flow Restriction Training on Tibial Bone Stress Injury Rehabilitation: An Exploratory Case Series - Andrew P Golden; Kathleen K Hogan; Jamie B Morris; Bryan B Pickens (International Journal of Sports Physical Therapy)
# Background